PENINGKATAN HASIL BELAJAR IPAS MELALUI MODEL DISCOVERY LEARNING PADA SISWA KELAS VI SDN 04 CUBADAK AIR KOTA PARIAMAN - Rizki, Muhammad; Amsari, Dina; Media, Afriza; Zuryanty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student learning outcomes in science subjects in elementary schools are still relatively low, requiring special attention in the learning process. This study aims to improve student learning outcomes through the application of the Discovery Learning model using classroom action research methods that combine quantitative and qualitative approaches. The study was conducted in two cycles: Cycle I, consisting of two meetings, and Cycle II, consisting of one meeting. The subjects were 22 sixth-grade students at SDN 04 Cubadak Air, Pariaman City. The results showed improvement in each cycle, as evidenced by the average learning outcome, which increased from 70 in Cycle I to 88 in Cycle II, the percentage of teaching module implementation from 72% to 93%, teacher activity from 73% to 94%, and student activity from 75% to 94%.